Social stratification and housing wealth inequality in transitional urban China. Issue 1 (2nd January 2021) - Yi, Chengdong; Li, Yuyao; Wang, Yourong; Wan, Haiyuan
ABSTRACT: As the Chinese economy continues to transform, housing wealth has gradually become the single largest asset in most urban households. At the same time, housing wealth inequality has worsened, and housing stratification has become a major form of social stratification in the country. However, there is no empirical evidence of temporal changes in housing wealth inequality and their implications on social stratification. Pooling three waves of survey data from the 1995, 2008, and 2013 iterations of the Chinese Household Income Project, we present a dynamic image of housing wealth inequality in urban China. The results suggest that housing wealth inequality decreased initially and increased later. To further illustrate how housing wealth is stratified by social groups, we conducted regression analyses and structural tests, which revealed three main results: the education level of the household head has an increasingly positive impact on housing wealth inequality; a household head with superior occupational status generally has an advantage in terms of possession of housing wealth with no evidence that this advantage diminishes during the transitional period; and income has a significant, positive impact on housing wealth, and this effect exhibited an increasing trend over time. These results imply that the temporal changes in housing wealth inequality exacerbated the social stratification in transitional urban China. Highlights This study explores the temporal changes of housing wealth inequality in urban China. Housing inequality decreased and then increased during the transitional period. Both education and income have increasingly positive impacts on the housing inequality. The advantages of the superior occupational status haven't diminished. These temporal changes exacerbated the social stratification in China.